Brachypodium distachyon BdPP2CA6 Interacts with BdPYLs and BdSnRK2 and Positively Regulates Salt Tolerance in Transgenic Arabidopsis - Zhang, Fan; Wei, Qiuhui; Shi, Jiaochun; Jin, Xia; He, Yuan; Zhang, Yang; Luo, Qingchen; Wang, Yuesheng; Chang, Junli; Yang, Guangxiao; He, Guangyuan (Frontiers in Plant Science, 2017)
The phytohormone abscisic acid (ABA) is essential in plant responding to biotic and abiotic stresses. Although ABA signaling model is well established in Arabidopsis, ABA receptor PYL family and clade A PP2C subfamily are not yet characterized in monocot model plant Brachypodium distachyon. In this study, we identified 12 PYLs and 8 clade A PP2Cs from B. distachyon genome and successfully cloned 12 PYLs and 7 clade A PP2Cs. Bioinformatic and expression analyses showed that most of the identified genes respond to several signal molecules and abiotic stresses. Protein–protein interaction analysis revealed that many BdPYLs and BdPP2CAs participate in the classic ABA-PYL-PP2C-SnRK2 signaling pathway. A clade A PP2C, designated BdPP2CA6, interacted with BdPYL11 in the absence of ABA and localized in nucleus. Most clade A PP2C members from Arabidopsis showed negatively regulation in ABA signaling pathway, whereas BdPP2CA6-overexpression transgenic Arabidopsis showed ABA hypersensitive phenotype, resulting in enhanced stomatal closure and salinity tolerance. Our results indicate that BdPP2CA6 positively regulates ABA and stress signal pathway in transgenic Arabidopsis plant seedlings.